Geochemical and Sedimentological Investigation of Possible Devonian-Mississippian Glaciation in the Appalachian Basin, Pennsylvania - Vollhardt, Heather; Fedorchuk, Nicholas; Morales, Ivianna; Cordie, David; Regan, Eric (Joint 72nd Annual Southeastern/ 58th Annual Northeastern Section Meeting - 2023, 2023)
The Late Paleozoic Ice Age (LPIA) was the last major icehouse climate (low CO2,...
Keywords: dept.esc

Gravitational resedimentation as a fundamental process in filling fjords: Lessons from outcrops from a late Palaeozoic fjord in Namibia - Menozzo da Rosa, Eduardo; Isbell, John L.; McNall, Natalie; Fedorchuk, Nicholas; Swart, Roger (Sedimentology, 2023)
The stratigraphic architecture of fjords is complicated due to the delicate interplay between ice dynamics, sediment supply, relative sea-level fluctuations and slope failures. Glaciogenic sediment is prone to failure and to be carried downslope to the fjord floor through the entire spectrum of mass movements and subaqueous density flows, as the unstable paraglacial submarine landscape moves towards stability. Palaeofjords formed by Gondwanan glaciers during the late Palaeozoic Ice Age contain a compelling record of gravitational resedimentation in fjord depositional systems. This paper showcases the geomorphology and depositional history of a glacial cycle in the Orutanda fjord in north-western Namibia as an example of an overdeepened fjord basin fill dominated by products of subaqueous gravitational processes. During glaciation, the Orutanda glacier carved a 20 km long by 3.7 km wide glacial trough that embodies an overdeepened basin. Ice thickness during terminal glacial occupation of the fjord is estimated to had been up to 200 m based on the fjord geomorphology. The progressive retreat of the tidewater glacier, concomitant with marine flooding, increased accommodation space in the overdeepened basin during deglaciation. During this stage, proglacial sedimentation through iceberg rafting and settling of turbid plumes was outpaced by intense paraglacial downslope resedimentation of glacially-transported debris. Successive failures from the fjord walls and downslope resedimentation resulted in coalescing debrite–turbidite lobes on the fjord floor. Slide deposits, composed entirely of deformed debrites and turbidites, indicate that these resedimented facies were prone to renewed mass wasting. As the Orutanda glacier melted, the fjord experienced the axial progradation of a fjord-head delta registered only by turbidites and slide deposits derived from its collapse. The Orutanda fjord sheds light on the relevance of paraglacial mass wasting in overprinting glaciogenic deposits. This insight is key to understanding the role of glaciers versus non-glacial processes in producing the glacial deep-time record.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/sed.13137
Keywords: Debris flows; Dwyka Group; dept.esc; late Palaeozoic Ice Age; mass wasting; paraglacial processes; peer-reviewed; turbidites

Reappraisal of Exceptionally Preserved S-Forms, Striae, and Fractures from Late Paleozoic Subglacial Surfaces in Paleofjords, NW Namibia - Fedorchuk, Nicholas D.; Isbell, John L.; Rosa, Eduardo L. M.; Swart, Roger; McNall, Natalie B. (Sedimentary Geology, 2023)
Determining the grounded ice dynamics of deep-time glaciations is limited by the scarcity of well-preserved subglacial erosional features and their irregular distribution. In particular, small-scale erosional features known as s-forms that are subglacially sculpted in bedrock by water and/or ice are rarely preserved from the pre-Cenozoic record. A detailed re-examination of two late Paleozoic (late Carboniferous–early Permian) glacially-polished, surfaces at the base of the Dwyka Gp. within paleofjords located in the Kaokoveld region of northwest Namibia reveals a range of erosional features including: complex, multi-directional striae that crosscut each other, crescentic markings, chattermark trails, sinuous furrows, linear furrows, transverse troughs, comma forms, sichelwannen, muschelbrüche, cavettos, a pothole, and rock drumlins. The first study location in the Sanitatis paleovalley is previously undescribed and consists of striae and fractures on a polished granite bedrock surface located on the paleovalley floor. Striae, crescentic markings, and chattermark trails indicate ice movement to the west/northwest (striae mean azimuth of 276°). The second location in the Hoarusib paleovalley was previously described and is located on a multi-level, resistant, quartzite bedrock ridge close to or on the valley wall. This location contains numerous s-forms, striae, and fractures, as well as onlapping glaciogenic sediments, including diamictite plastered within a pothole. Some of these features are superimposed on rock drumlins. These erosional features were likely formed by a combination of pressurized subglacial meltwater and glacial abrasion underneath a glacier as it flowed over and around a resistant bedrock outcrop. Orientations of striae and chattermark trails at the second location indicate a primary direction of ice movement toward the west/northwest (striae modal azimuth of 275°), a minor secondary movement to the southwest (255°), and abundant third-order striae indicating ice flow around bedrock obstacles. However, cross-cutting relations suggest the primary and secondary striae orientations are not related to two distinct glacial advances as previously thought. The complex relationships between striae, fractures, and s-forms suggest that a combination of pressure melting, abundant subglacial meltwater, debris-rich basal ice, and variable ice flow paths around resistant obstacles was required to form these features. We conclude that the study locations were overridden by relatively thick (>210 m) warm-based or polythermal glaciers that were confined to a network of fjords as ice receded and stagnated. The glaciers flowed west into present-day Brazil during the late Paleozoic and likely overtopped the paleovalley walls during times of ice maxima.
1 citations (Crossref) [2023-10-31]
Keywords: Carboniferous; Dwyka; Erosional; Fjords; Glacial; Permian; dept.esc; peer-reviewed

Reassessing a glacial landscape developed during terminal glaciation of the Late Paleozoic Ice Age in Uruguay - Isbell, John L.; Fedorchuk, Nicholas D.; Rosa, Eduardo L. M.; Goso, César; Alonso-Muruaga, Pablo J. (Sedimentary Geology, 2023)
Whalebacks, roche moutonnées, and S-forms carved on Ediacaran granitoids near Cerro de las Cuentas, Uruguay, along with overlying diamictites, siltstones, and sandstones displaying soft-sediment grooved and striated surfaces in the Pennsylvanian San Gregorio Formation, record the glacial to post-glacial transition in the linked Norte, southern Paraná and Chaco-Paraná basins of Uruguay, Brazil, and Argentina respectively. Early authors reported these features resulted from subglacial abrasion and deposition as lodgement tills and glaciotectonites. Our re-examination reveals a nuanced setting with changing ice thicknesses, subglacial kinematics, and ice proximal glaciomarine dynamics associated with advance and retreat of an ice stream, or multiple advances of the Uruguayan Ice lobe, during glaciation of the Late Paleozoic Ice Age (LPIA) in these basins. The preserved landforms indicate temperate glacial conditions. Whalebacks formed under 1.6 to 2.5 km-thick ice and likely formed when the lobe extended across the Uruguayan and Rio Grande do Sul shields into the adjacent Paraná Basin. Previously unidentified m-scale roches moutonnées cut into one whaleback developed under thinner ice where reduced basal pressure allowed for the opening of air and water-filled cavities, thus facilitating quarrying on the lee side of basement bumps. S-forms provide additional evidence for the occurrence of subglacial waters, indicating that the basal ice was at or above its pressure melting point. The lower meter of the overlying strata consists of interstratified trace fossil-bearing, laminated siltstones; thin-bedded diamictites; and current-rippled sandstones. Trace fossils belonging to the Mermia ichnofacies within the basal siltstones, as well as acritarchs in the overlying siltstones, suggest that these sediments were deposited in ice-proximal subaqueous settings with contributions from meltwater discharge. Graded siltstone laminae suggest settling from suspension likely from meltwater plumes, while thin-bedded diamictites were deposited either as debris flows or as two-component sedimentation with fines settling from suspension and coarser particles introduce as iceberg-rafted dropstones. Current-rippled sandstones indicate the occurrence of underflow currents. Soft-sediment troughs, grooves, and striations cutting these sediments display curved and sinuous paths with some features oriented perpendicular, and one oriented opposite to the overall trend. They contain marginal and terminal berms typical of iceberg scour marks suggesting transit across the area by icebergs calving from a tidewater ice front located to the SE.
3 citations (Crossref) [2023-10-31]
Keywords: Iceberg keel marks; Late Paleozoic Ice Age; Roche moutonnées; San Gregorio Fm; Uruguayan Ice Lobe; Whalebacks; dept.esc